Study of Thyroid Function Status in Type 2 Diabetic Patients (KYAMC Journal, 2019)
Background: Thyroid dysfunction specially hypothyroidism may occur in type 2 diabetic patients.Objective: To observe thyroid function status in type 2 diabetic patientsMaterials and Methods: This cross sectional study was carried out in the Department of Physiology, Sir Salimullah Medical College, Dhaka from July 2016 to June 2017. Total 60 subjects including male and female, age ranged from 40 to 60 years were included in this study, among them 30 were non-diabetic subjects and 30 were type 2 diabetic patients.Results: In this study, mean serum TSH level was significantly (p